Update on therapies for metastatic melanoma - Sondak, Vernon K. (Henry Stewart Talks, 2013)
Overview of new treatments approved for advanced melanoma in the past few years, Pegylated interferon alfa-2b, Ipilimumab, Mechanism of action, Impact on progression-free and overall survival, Overview of immune-related adverse events, Vemurafenib, Mechanism of action, Impact on progression-free and overall survival, Induction of secondary squamous cell carcinomas, Possible role for combined RAF/MEK inhibition, A "standard" approach to treatment of stage IV melanoma